Toxoplasma gondii actively remodels the microtubule network in host cells - Walker, Margaret E. (2008)
Toxoplasma gondii infection triggers host microtubule rearrangement and organelle recruitment around the parasite vacuole. Factors affecting initial stages of microtubule remodeling are unknown. To illuminate the mechanism, we tested the hypothesis that the parasite actively remodels host microtubules. Utilizing heat-killed parasites and time-lapse analysis, we determined microtubule rearrangement requires living parasites and is time dependent. We discovered a novel aster of microtubules (MTs) associates with the vacuole within 1 h of infection. This aster lacks the concentrated foci of gamma (γ)-tubulin normally associated with MT nucleation sites. Unexpectedly, vacuole enlargement does not correlate with an increase in MT staining around the vacuole. We conclude microtubule remodeling does not result from steric constraints. Using nocodazole washout studies, we demonstrate the vacuole nucleates host microtubule growth in-vivo via γ-tubulin-associated sites. Moreover, superinfected host cells display multiple γ-tubulin foci. Microtubule dynamics are critical for cell cycle control in uninfected cells. Using non-confluent monolayers, we show host cells commonly fail to finish cytokinesis resulting in larger, multinucleated cells. Our data suggest intimate interactions between T. gondii and host microtubules result in suppression of cell division and/or cause a mitotic defect, thus providing a larger space for parasite duplication.